PANGLIMA LAOT AND THE MODEL OF SOCIAL CONFLICT RESOLUTION IN FISHERMEN COMMUNITIES IN BIREUEN, INDONESIA - Rauzana Hilda; M. Nazaruddin; Fakhrurrazi; Ibrahim Chalid; Kurniawati (Master Program of Sociology, Universitas Malikussaleh,, 2026)
This study examines the social conflict resolution model in the fishing community of Lhok Simpang Mamplam, Bireuen Regency. The focus of the study is on conflicts that occur between fishermen, particularly during the peak fishing season when competition for territorial fishing grounds escalates. This study aims to identify local wisdom in dispute resolution and analyze the settlement model applied in the local fishing community. The study used qualitative methods with a descriptive approach. Data were obtained through in-depth interviews, non-participatory observation, and documentation studies. The research informants consisted of the Panglima Laot (the Commanders of the Sea), fishermen, and community leaders who were selected purposively. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that dispute resolution in Lhok Simpang Mamplam is carried out through customary law mechanisms led by the Panglima Laot. Forms of local wisdom identified include suloh, customary deliberation, peusijuk, and peumat jaroe, all of which are part of the peacemaking and social restoration process. Dispute resolution models are implemented in stages, depending on the level of the problem, from direct agreement between the parties to customary deliberation. Research findings show that the dispute resolution played by Panglima Laot based on local wisdom is still effective in maintaining order, strengthening social cohesion, and preventing the spread of conflict among fishing communities.